(Re)figurações de Iara: investigando o medo e o fascínio pelas sereias da antiguidade ao fantasismo - Rosa Junior, Paulo Ailton Ferreira da (2024)
For at least two centuries the character “Iara” or “Mãe d’água”, also known as “Brazilian Mermaid”, has been parading its beauty and its horrors in works from authors of our literatures as one the most meaningful facts borrowed from the Brazilian folklore. It is known that it takes shape from the meeting of the imagination of the tradition of our colonizers with that of original people from here, thus having in oral literature what could be called an original representation. If we consider, from Reis (2018), that figuration is the primary representation of a certain character and refiguration a way of reimagining this character in new and different narratives, the objective of this research was to investigate the different refigurations of the character “Iara” or “Mãe D'água”, from Romanticism to the Contemporary movement of production and defense of a Brazilian Fantastic Literature called Fantasismo, to understand the permanences and differences between them. It was not possible to make this movement without thinking about the possible influences that “Iara” or “Mãe D’água” may have inherited from related beings from other traditions, such as Atlantic mermaids and Homeric sirens. Therefore, methodologically I start from texts from Classical Antiquity, such as the Odyssey and the Argonautics, to understand who the Sirenas, or Homeric mermaids, were; I explore medieval bestiaries and texts from the 17th and 18th centuries to understand how Atlantic mermaids were configured in the literature of the time; I revisit the work of Câmara Cascudo, an important Brazilian folklorist, to try to give shape to “Iara” or “Mãe D’água” in our culture; I observe authors from Romanticism and Modernism, such as José de Alencar and Monteiro Lobato, in order to understand how they contributed to the affirmation of the character in our imagination; and, finally, I present an interpretative reading of three works of contemporary fantastic literature – Sete Monstros Brasileiros, from Bráulio Tavares, The Elephant and Macaw Banner, from Christopher Kastensmidt, e O Legado Folclórico, from Felipe Castilho – by dedicating attention to how they reimagine “Iara” or “Mãe D’água” in production contexts that are very different from the first ones in which it appeared. Based on the resulting investigations surrounding the case studied, I defend the thesis that contemporary Brazilian fantasy literature, by refiguring “Iara”, continues a very old process that is at the heart of the character's own origin, that of the adaptation of a very old argument, that of the water monster woman, to new contexts and new narratives, also creating its own variations of the mythical figure by embodying new versions of the Brazilian mermaid inspired by current narrative genres. Thus, Iara or Mãe D’água is understood as the particular form that the Brazilian imagination gave, based on external referents, to the timeless fear of female insurrection against male power and the appeal to heterosexual desire as a weapon for this; as well as national written literature, the vehicle responsible for offering body to this character in our culture and a new breath of fresh air in contemporary times.